Impact of biocontrol agents on the health of garden pea (Pisum sativum) in Kumaon hills of Himalayas - HOODA, K S; BHATT, J C; JOSHI, D; SUSHIL, S N; GUPTA, J S (The Indian Journal of Agricultural Sciences, 2011)
In a field evaluation conducted on garden pea (Pisum sativum L.), Trichoderma viride, Trichoderma harzianum, Pseudomonas fluorescens, mixture of T. harziantim and P. jluorescens, Aspergillus niger and carbendazim showed significantly higher seedling emergence and vigour as compared with check, maximum emergence (71.2%) and vigour (1 623) being with seed treatment of T. viride @ 0.4%. All the treatments also significantly reduced seed and seedling rot, wilt and resulted in significantly higher yield over check, T. viride @ 0.4% being best by recording lowest seed and seedling rot (28.9%) and wilt (4.7%) compared with check. Foliar sprays of bioagents exhibited phytotonic effect on the plants without any significant impact on the severity of leaf blight and powdery mildew,